2019
DOI: 10.1021/acs.nanolett.9b00975
|View full text |Cite
|
Sign up to set email alerts
|

NIR-Responsive Polypeptide Nanocomposite Generates NO Gas, Mild Photothermia, and Chemotherapy to Reverse Multidrug-Resistant Cancer

Abstract: Multidrug resistance (MDR) of cancers that results from overexpression of a P-glycoprotein (P-gp) transporter mainly causes chemotherapy (CT) failure and hinders clinical transitions of current polypeptide nanomedicines. Herein, a novel polypeptide nanocomposite PNOC-PDA that integrates heat-sensitive NO gas delivery and photothermal conversion attributes can overcome MDR and maximize CT; meanwhile the optimized CT and intracellular high-concentration NO gas can assist a mild photothermal therapy (PTT) to erad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 39 publications
0
93
0
2
Order By: Relevance
“…These multifunctional nanocomposites integrating photothermal, chemo-, and gene therapy successfully caused regression in triple-negative breast cancer with negligible side effects. Very recently, Dong et al reported a novel polypeptide nanocomposite PNOC-PDA/DOX by coating PDA on micelles formed by S-nitroso (SNO, a kind of heatsensitive NO donor) conjugated polypeptide copolymer and further loading with DOX (Ding et al, 2019). Upon NIR light irradiation, NO gas was released due to heat-induced S-NO cleavage.…”
Section: Organic Nanomaterials-based Chemo-photothermal Therapymentioning
confidence: 99%
“…These multifunctional nanocomposites integrating photothermal, chemo-, and gene therapy successfully caused regression in triple-negative breast cancer with negligible side effects. Very recently, Dong et al reported a novel polypeptide nanocomposite PNOC-PDA/DOX by coating PDA on micelles formed by S-nitroso (SNO, a kind of heatsensitive NO donor) conjugated polypeptide copolymer and further loading with DOX (Ding et al, 2019). Upon NIR light irradiation, NO gas was released due to heat-induced S-NO cleavage.…”
Section: Organic Nanomaterials-based Chemo-photothermal Therapymentioning
confidence: 99%
“…Alternatively, AuNR is encapsulated in polymer micelles as reported by Song et al in their design of PLGA micelles coloaded with reduced graphene oxide (rGO) and DOX. [260] PDA also serves as an effective agent in inducing photothermal disassembly as applied for DOX delivery by Ding et al [261] In its another application, Zhang et al designed PDA-coated AuNR loaded with cisplatin in the PDA layer, [259] and further modified by conjugation with c(RGDyC), a targeting ligand for v 3 integrin tumor biomarker. They demonstrated an NIR-induced antitumor effect by hyperthermia and cisplatin release in v 3 (+) tumors.…”
Section: Polymer Micelle Loaded With Photothermal Npmentioning
confidence: 99%
“…AuNR@mSiO 2 Au (NIR) Naproxen [ 243] mSiO 2 @Au Au (808) Ibuprofen [ 242] AuNR@mSiO 2 Au (543) DOX [ 244] UCN@mSiO 2 Carbon dot (980) DOX, ZnPc [ 249] HAuNS Au (808) DOX, combretastatin A-4 phosphate, paclitaxel, cisplatin, siRNA [ 75,79] [ 83,84,247] AuNC Au (808) DOX [ 78,79] Disassembly Liposome AuNP (Vis) Berberine [ 250] Liposome Black phosphorous (808) DOX [ 251] Polymer micelle Cypate (NIR) Pt (IV) prodrug [ 252] Polymer micelle Indocyanine (808) Cisplatin [ 254] Polymer micelle Indocyanine (808) DOX [ 253] Polymer micelle AuNR (808) DOX [ 257,258] Polymer micelle AuNR, GO (808) DOX [ 260] Polymer micelle PDA (808) DOX, NO [ 261] Polymer micelle BODIPY (NIR) Camptothecin [ 255] PDA-RGD AuNR, PDA (NIR) Cisplatin [ 259] Polymer micelle AuNF (800) Rhodamine [ 266] Polymer micelle Au (808) siRNA (GFP) [ 267] AuNR@dsDNA AuNR (1064) Plasmid DNA [ 256] AuNS@oligo Au (808) DNAzyme [ 262] Hydrogel Indocyanine green (NIR) DOX [ 268] Hydrogel AuNP (NIR) Bevacizumab [ 269] Hydrogel Pt@dendrimer (NIR) Bortezomib [ 270] Hydrogel GO (808) Camptothecin, 5-FU [ 263] Hydrogel Black phosphorous (808) DOX [ 271] Hydrogel Thiophene polymer (915) DOX [ 272] Hydrogel-chitosan Poly(dopamine) (808) Ciprofloxacin [ 284] Microsphere Poly(pyrrole) (808) Vancomycin [ 287] Silica nanocapsule Fe 3 O 4 (NIR) DOX [ 274] Silica nanocapsule AuNP (NIR) Rhodamine [ 245] mSiO 2 @Au Au (NIR) dsDNA…”
Section: Gatingmentioning
confidence: 99%
“…Qiu等人 [37] 合成的纳米材料Ir@Fe3O4 NPs, 可以将NIR [18,19,22,23,26,27] . 这一机制可以弥补单一 MPTT抗癌疗效有限的缺点, 同时也解决了抗癌药物在 肿瘤组织有效浓度不高、肿瘤靶向性差等临床难题.…”
Section: 与常规Ptt中高温诱导细胞坏死不同 Mptt通常unclassified
“…Song等人 [32] 将PI3K 抑制剂LY294002装载入Bi 2 S 3 -Tween 20纳米材料中, HSP70的表达来激活BAX/BAK介导的线粒体途径细 胞凋亡, 从而有效杀死大肠癌细胞. Zhang等人 [33] 和 Ding等人 [23] 则将NO用于MPTT, 在NIR照射下触发纳 米材料释放NO, 从而诱导细胞凋亡. Figure 5 (Color online) The new theory of "Nezha"-Tumor Photothermal Therapy.…”
Section: 温和光热疗法联合其他疗法unclassified